2018
DOI: 10.3390/f9110704
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Abandonment of Forest Management Has a Strong Impact on Tree Morphology and Wood Volume Allocation Pattern of European Beech (Fagus sylvatica L.)

Abstract: The three-dimensional (3D) morphology of individual trees is critical for light interception, growth, stability and interactions with the local environment. Forest management intensity is a key driver of tree morphology, but how the long-term abandonment of silvicultural measures impacts trunk and crown morphological traits is not fully understood. Here, we take advantage of a long management intensity gradient combined with a high-resolution terrestrial laser scanning (TLS) approach to explore how management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Tree structure, on the other hand, can be characterized by using morphological measures such as crown dimension (e.g., volume, surface area) and stem attributes (e.g., diameter at breast height (DBH), height, height of crown base) (Pretzsch, 2014). The availability of 3D point clouds from terrestrial laser scanning (TLS) has provided an effective means for such measurements allowing TLS to be utilized in generating stem and crown attributes (Bayer et al, 2013;Calders et al, 2013Calders et al, , 2018Georgi et al, 2018;Juchheim et al, 2017;Liang et al, 2012;Metz et al, 2013;Saarinen et al, 2017Saarinen et al, , 2020Seidel et al, 2011). However, objective and quantitative measures for structural complexity of individual trees are needed to better understand relationship between forest structural diversity and ecosystem services such as biodiversity, productivity, and carbon uptake (Hardiman et al, 2011;Messier et al, 2013;Puettmann et al, 2015;Zenner, 2015).…”
mentioning
confidence: 99%
“…Tree structure, on the other hand, can be characterized by using morphological measures such as crown dimension (e.g., volume, surface area) and stem attributes (e.g., diameter at breast height (DBH), height, height of crown base) (Pretzsch, 2014). The availability of 3D point clouds from terrestrial laser scanning (TLS) has provided an effective means for such measurements allowing TLS to be utilized in generating stem and crown attributes (Bayer et al, 2013;Calders et al, 2013Calders et al, , 2018Georgi et al, 2018;Juchheim et al, 2017;Liang et al, 2012;Metz et al, 2013;Saarinen et al, 2017Saarinen et al, , 2020Seidel et al, 2011). However, objective and quantitative measures for structural complexity of individual trees are needed to better understand relationship between forest structural diversity and ecosystem services such as biodiversity, productivity, and carbon uptake (Hardiman et al, 2011;Messier et al, 2013;Puettmann et al, 2015;Zenner, 2015).…”
mentioning
confidence: 99%
“…Our results did not reveal notable difference in form factor between moderate and intensive thinning whereas tapering below 50% of tree height was smaller for moderate thinnings than for intensive thinnings corroborating results by Jacobs et al (2019). Georgi et al (2018) found significant difference in tapering generated from TLS data between unmanaged and intensively managed beech stands. Most of their attributes were related to crown dimensions or height of branches similar to the study by Juchheim et al (2017) who concentrated on crown expansion in both horizontal and vertical directions.…”
Section: Discussionmentioning
confidence: 81%
“…In applications related to boreal forests, TLS has been utilized in quantifying stem growth and changes in stem taper (Luoma et al 2019), reparametrizing an existing taper curve model , and assessing timber quality . In Central Europe, on the other hand, impacts of silviculture on stem form of Norway spruce (Jacobs et al 2019) and European beech (Juchheim et al 2017, Georgi et al 2018, Noyer et al 2019) have been studied. In Juchheim et al (2017) and Georgi et al (2018), several attributes characterizing stem size and form were generated from TLS point clouds (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earlier generations of laser scanners, however, mostly lack a high-resolution acquisition of the complex tree crowns in dense mature forests. In this study we make use of state-of-the-art technology of fullwaveform TLS with online waveform processing to measure a large number of individual trees in a highly accurate manner (Bienert et al 2018;Georgi et al 2018).…”
Section: Introductionmentioning
confidence: 99%